Time-course changes in cell proliferation, cell differentiation and cell death in the avian, amphibian and mammalian brains - Pilani Nkomozepi (My University, 2019)
This thesis presents a collection of four related studies that were designed to investigate the occurrence and dynamics of postnatal neurogenesis in animal species derived from three different vertebrate taxa: mammals, avians, and amphibians. This work was prompted by the observation that non-mammalian vertebrates are able to regenerate functional neural tissue following injury or experimental ablation of whole or parts of the brain parts, in striking contrast to mammals where neural tissue is seldom replaced following injury, (Abbreviation abstract)
A thesis submitted to the faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of doctor of Philosophy